Pedagogiczne i prawne działania podejmowane w Polsce wobec osób uzależnionych od alkoholu - Karaszewska , Hanna; Rajewska de Mezer , Joanna; Silecka-Marek , Ewelina (Studia Edukacyjne, 2018)
The issue of alcohol consumption, addiction to it, and causes and effects of this phenomenon have already been explored many times. The article describes current pedagogical and legal activities taken in Poland towards people addicted to alcohol and related controversy . The authors drew attention to a number of problems concerning with alcohol addiction for an alcohol abuse person and his family. Starting from the current law on upbringing in sobriety and counteracting alcoholism because it takes up issues related to treatment, rehabilitation and social reintegration of people addicted to alcohol. There are institutions established on its basis and take up actions aimed at diagnosing the problem of an individual’s addiction to alcohol, leading to a ruling and requiring the person addicted to alcohol to undergo treatment. In the article the stages of treatment have been described in detail, requriments, important person for example probation officer and possible to receive treatment from non-governmental organizations that help those addicted and thus create an option for those addicted to alcohol to self-organize. The authors emphasized that the process of freeing from alcohol addiction is incredibly difficult and sometimes prolonged. Thus, the compulsory character of rehab treatment sparks a lot of controversy, as it contradicts the right to self-determination, i.e. independent decision of the person addicted to take up the treatment. There is a need to search new solutions in this respect, develop tools that increase the effectiveness of activities taken towards those addicted and exchange experiences on the global scale.